Factors Influencing Sichuan Consumers' Purchase Intention on E-Commerce in the Apparel Industry - Changhao Xiao (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This study investigates the factors influencing Sichuan consumers' purchase intention on e-commerce in the apparel industry. The economic advantages of live streaming and e-commerce have attracted widespread attention, and researchers are particularly keen on delving into the psychological impact of these new channels on consumers' buying behavior. The emergence of new sales channels in the apparel sector is increasingly vital in stimulating sales growth. The number of respondents for this study was 395. The results of this study show that consumers’ purchase intention for e-commerce in the apparel industry would be impacted by performance expectation, effort convenience, perceived usefulness, perceived behavior control expectation, and social impact. These findings have practical implications for marketers and e-commerce platforms, enhancing the consumer experience and increasing purchase intention.